KULIAH KERJA NYATA TEMATIK (KKNT)SEMESTER GANJIL TAHUN AKADEMIK 2025/2026 DI DESA BANYU URIP KECAMATAN TANJUNG LAGO KABUPATEN BANYUASIN - Ade Putra; Rangga, Rangga; Vini Ina Safitri; Siti Rahmah Ayu; Resa Putri Raflesia; Nadia Angelina Silitona; Maya Safitri; M. Kelvin; Rizky Sabilillah (JURNAL PENGABDIAN MANDIRI, 2025)
xx